Visual Performance Correlation with Corneal Aberrometric Profile and Pupil Size After Implantation of a Trifocal Hydrophobic IOL - Bosc C; Le Maléfan E; Boury P; Bernier M; Barrucand A (Clinical Ophthalmology, 2024)
Camille Bosc, Eloïse Le Maléfan, Pauline Boury, Mélanie Bernier, Anne Barrucand Département de Recherche Clinique, Institut Ophtalmologique de l’Ouest (IOO) Jules Verne, Nantes, FranceCorrespondence: Camille Bosc, Département de Recherche Clinique Institut Ophtalmologique de l’Ouest (IOO) Jules Verne, 2/4 Route de Paris, Nantes, 44300, France, Email recherche@ophtalliance.frPurpose: To evaluate clinical outcomes obtained after cataract surgery involving the implantation of a trifocal hydrophobic intraocular lens (IOL) and to determine if pupil size and the corneal aberrometric profile correlate to visual acuity at different distances.Methods: 49 patients (98 eyes) underwent bilateral cataract surgery with the placement of FineVision HP IOLs for presbyopia and were assessed at 1- and 3- to 6-months post-surgery. Postoperatively, refraction, monocular and binocular uncorrected and corrected distance visual acuity (UDVA and CDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA) and the binocular defocus curve were measured. Pupil size and corneal aberrations (higher-order and low-order aberrations; HOA and LOA) were also measured using a Scheimpflug 3D camera.Results: Sphere, cylinder and spherical equivalent decreased significantly after surgery (p< 0.05) and CDVA had improved significantly 1-month post-surgery (p=0.007). The sphere, cylinder, spherical equivalent and CDVA values remained stable at the 3- to 6-month follow-up (p> 0.05). Binocular UDVA was 0 logMAR or better for 79.2% of patients and binocular UNVA was 0.1 logMAR or better for 91.7%. The binocular defocus curve showed average maximum visual acuity values at – 0.07± 0.06 logMAR, 0.01± 0.06 logMAR, and 0.01± 0.06 logMAR, for far, intermediate and near distances, respectively. Neither the UDVA nor UNVA values correlated with patient pupil diameter (UDVA: r=0.035, p=0.744; UNVA: r=− 0.073, p=0.492). Neither the UDVA nor UNVA values correlated with patient HOA or LOA (UDVA versus HOA: r=0.016, p=0.872; UDVA versus LOA: r=0.032, p=0.759; UNVA versus HOA: r=0.056, p=0.582; UNVA versus LOA: r=0.059, p=0.568).Conclusion: This study shows that the FineVision HP IOL provides excellent refractive and visual outcomes at different distances. Pupil size does not correlate with UDVA and UNVA and quality of vision does not seem to correlate with the corneal aberrometric profile.Keywords: aberrations, pupil size, intraocular lens, trifocal, diffractive, hydrophobic